Thermochromic perovskite intelligent photovoltaic window and preparation method thereof
By adopting the structure of translucent perovskite solar cell layer, thermochromic layer and color transparent film layer in perovskite smart photovoltaic window, the multi-layer skin structure of chameleon is simulated, and the reversible change in color and transparency is achieved, and the current solution is to solve the problem of There are problems of unstable performance and insufficient aesthetics of perovskite smart photovoltaic windows in the technology, which improves the cyclic stability and photovoltaic power generation performance of the device.
Patent Information
- Application Number
- CN202411192302.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-20
AI Technical Summary
The existing perovskite smart photovoltaic windows are unstable after multiple cycles of discoloration, and the multi-layer structure can only achieve transparency changes, which cannot meet the aesthetics and technological needs of modern buildings. The translucent photovoltaic devices are flexible The brittleness and high-temperature annealing requirements in the device limit their development.
Using the structure of translucent perovskite solar cell layer, thermochromic layer and color transparent film layer stacked in sequence, simulates the multi-layer skin structure of the chameleon, and achieves a reversible change in color and transparency through temperature changes to avoid the photovoltaic layer being discolored. function to improve cycle stability and balance transparency and photoelectric conversion efficiency by optimizing interlayer design and material selection.
The reversible transformation of perovskite smart photovoltaic windows between different colors and transparency has been achieved, which improves the cyclic stability of the device and photovoltaic power generation performance, and meets the aesthetic and technological needs of modern buildings.
Smart Images

Figure CN119173058A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photothermal technology, and in particular to a thermochromic perovskite smart photovoltaic window and a preparation method thereof. Background Art
[0002] In recent years, perovskite solar cells have attracted widespread attention due to their outstanding photoelectric conversion efficiency, adjustable color, high transmittance and other characteristics. In addition, since some perovskite materials can respond to external stimuli and exhibit reversible optical properties, perovskite solar cells can be integrated with windows of buildings, cars, etc. to obtain perovskite smart windows that store energy and save energy, which is conducive to promoting the development of energy-saving buildings and energy-saving cars and improving energy efficiency.
[0003] Perovskite smart photovoltaic windows can be divided into two categories according to the color-changing principle: the first category is the use of perovskite solar cells that have both smart color-changing and photovoltaic power generation characteristics; the second category is a multilayer perovskite smart photovoltaic window that integrates semi-transparent perovskite solar cells with additional color-changing components. For the first type of perovskite smart photovoltaic window, due to the stability of the perovskite material itself, and repeated phase changes or material reorganization may cause irreversible degradation of the perovskite material, the perovskite smart photovoltaic window device cannot maintain the stability of battery performance and the durability of optical performance after multiple cycles of color change. The second type of perovskite smart photovoltaic window often uses thermochromic devices as color-changing components. Although the thermochromic multilayer perovskite smart photovoltaic window can have relatively high cycle stability, its cycle stability still needs to be improved. In addition, the multilayer perovskite smart photovoltaic window often only has changes in transparency, and cannot achieve transitions between different colors, and cannot meet the aesthetic and technological requirements of modern buildings.
[0004] For multilayer perovskite smart photovoltaic windows, their optoelectronic performance often depends on the semi-transparent perovskite solar cells therein. However, in semi-transparent photovoltaic devices, it is still challenging to achieve high transparency to visible light and efficient solar energy conversion at the same time. Indium tin oxide (ITO) is currently the most commonly used top transparent electrode in semi-transparent photovoltaic devices. However, its inherent brittleness makes it easy to crack under repeated bending, limiting its development in flexible devices. In addition, high-quality ITO films require higher annealing temperatures, which can easily damage the underlying perovskite solar cell functional layers. Ultra-thin and highly conductive metal films are considered to be ideal for transparent top electrodes due to their high visible light transparency, excellent conductivity, and high-temperature stability. For the ultra-thin metal electrodes currently used in semi-transparent perovskite solar cells, how to balance their transparency and resistance will affect the transparency, color change effect, and photoelectric conversion efficiency of the entire perovskite smart photovoltaic window. Summary of the invention
[0005] The present invention provides a thermochromic perovskite intelligent photovoltaic window and a preparation method thereof, so as to solve the above-mentioned problems existing in the prior art.
[0006] According to a first aspect of the present invention, the present invention provides a thermochromic perovskite smart photovoltaic window, comprising a semi-transparent perovskite solar cell layer, a thermochromic layer and a colored transparent film layer stacked in sequence; the semi-transparent perovskite solar cell layer and the colored transparent film layer have different colors.
[0007] In the above scheme, the thermochromic perovskite smart photovoltaic window of the present invention comprises a semi-transparent perovskite solar cell layer, a thermochromic layer and a colored transparent film layer stacked in sequence, which simulates the multi-layer skin structure of a chameleon. The combined effect of the multi-layer structure enables the smart photovoltaic window to present different colors: at 20-30°C (for example, 25°C), the color of the perovskite smart photovoltaic window is a composite color of the colors of the semi-transparent perovskite solar cell layer and the colored transparent film layer, and has a high transparency. At 40-50°C (for example, 45°C), due to the effect of the low-transparency thermochromic layer, the perovskite smart window The color of the photovoltaic window changes, showing the color of the semi-transparent perovskite solar cell layer, and the transparency is low. As the temperature changes alternately between day and night, the thermochromic perovskite smart photovoltaic window undergoes a reversible change between two colors and transparency, thereby meeting the aesthetic and technological requirements of modern architecture; by avoiding the photovoltaic layer from assuming the color change function, the effect of the color change process on the photovoltaic power generation performance of the perovskite layer is reduced, and the overall cycle stability of the device is finally improved; by balancing the transparency and photoelectric conversion efficiency of the semi-transparent perovskite solar cell layer, the transparency and photovoltaic power generation performance of the thermochromic perovskite smart photovoltaic window are improved. Finally, through the synergistic effect of the semi-transparent perovskite solar cell layer, the thermochromic layer and the colored transparent film layer, the thermochromic perovskite smart photovoltaic window of the present invention can simultaneously have multiple functions of photovoltaic power generation, color change and transparency change, and has high cycle stability.
[0008] In order to achieve the transition between different colors, further, the color of the semi-transparent perovskite solar cell layer includes yellow, red, blue or colorless and transparent; the color of the colored transparent film layer includes blue, red, yellow, green or purple.
[0009] In order to better improve the photovoltaic power generation performance, color change and transparency change functions of the thermochromic perovskite smart photovoltaic window, further, the semi-transparent perovskite solar cell layer satisfies at least one of the following characteristics (1)-(3): (1) The average visible light transparency in the visible light range (360-780nm) is >30%, preferably 40-50%; (2) Photoelectric conversion efficiency is >1%, preferably 8-15%; (3) Light utilization efficiency (LUE) is 2.0-6.0, preferably 4.0-5.8.
[0010] Furthermore, the semi-transparent perovskite solar cell layer includes a transparent bottom electrode layer, an electron transport layer, a perovskite absorption layer, a hole transport layer and a transparent top electrode layer stacked in sequence, and the stacking method includes a formal structure and a transverse structure.
[0011] Preferably, the material of the transparent bottom electrode layer includes one or more of ITO, FTO and AZO, and its thickness is 90-120nm; the material of the electron transport layer includes one or more of SnO2, PCBM, ZnO, TiO2, and its thickness is 20-60nm; the thickness of the perovskite absorption layer is 80-500nm; the material of the hole transport layer includes one or more of Spiro-OMeTAD, PTAA, SAM-type single molecules, PEDOT:PSS, nickel oxide, and its thickness is 100-200nm; in a specific embodiment, the electron transport layer can be SnO2, and the hole transport layer can be Spiro-OMeTAD.
[0012] In the above scheme, by making a special interlayer design for the semi-transparent perovskite solar cell layer, the overall performance of the semi-transparent perovskite solar cell layer can be improved, so as to better cooperate with the thermochromic layer and the colored transparent film layer, and realize the photovoltaic power generation, color change and transparency change of the thermochromic perovskite smart photovoltaic window and high cycle stability. Further, by limiting the thickness and transparency of each layer within a reasonable range, the layers can play a better synergistic role, thereby better improving the overall performance of the semi-transparent perovskite solar cell layer.
[0013] Furthermore, the method for preparing the semi-transparent perovskite solar cell layer comprises the following steps: First, an electron transport layer solution is spin-coated on the transparent conductive substrate at a speed of 3000-5000 rpm, and then heated and annealed to form an electron transport layer.
[0014] Then, the perovskite absorption layer is prepared by a two-step method. Taking the CsPbBr3 perovskite absorption layer as an example, 1M PbBr2 / DMF solution is spin-coated on the electron transport layer at a speed of 3000-5000 rpm for 20-40s, and then heated and annealed on a heating plate at 90-110°C for 20-40min to form a PbBr2 film.
[0015] Then, a CsBr solution with a concentration of 200-300 mg / mL is dripped onto the PbBr2 film, left for 10-30 seconds (preferably 10-20 seconds, more preferably 15 seconds), and then spin-coated for 20-40 seconds. After heating and annealing on a hot plate at 250°C-300°C for 3-8 minutes, the film is immersed in an isopropyl alcohol (IPA) solution for 20-40 minutes, and then heated and annealed again on a hot plate at 250°C-300°C for 10-20 minutes.
[0016] The hole transport layer solution is then spin-coated on the perovskite absorption layer to form a hole transport layer.
[0017] Finally, a transparent top electrode layer material is deposited on the hole transport layer.
[0018] In order to improve the overall performance of the semi-transparent perovskite solar cell layer, further, the transparent top electrode layer has an average visible light transparency of >50% in the visible light range of 360-780nm and a square resistance of <20Ω / m 2 ; Preferably, the material of the transparent top electrode layer includes one or more of metal, metal oxide, and conductive polymer; More preferably, the transparent top electrode layer is made of an ultra-thin metal material, and the material of the ultra-thin metal layer includes one or more of Au, Ag, Al, Cu, and Cr.
[0019] The present invention uses Au as an ultra-thin metal transparent top electrode to prepare a semi-transparent perovskite solar cell. Generally, the light transmittance of an ultra-thin metal conductive film can be improved by reducing its thickness. However, when the thickness of the Au film is less than 10 nm, its discontinuous growth on a heterogeneous substrate will result in a higher resistivity, affecting the efficiency of the overall device. Therefore, in order to ensure that the ultra-thin metal has a higher light transmittance and a lower resistance, the present invention adds an oxide or sulfide buffer layer between the ultra-thin metal layer and the hole transport layer to achieve continuous growth of an Au film with a thickness of less than 10 nm, thereby achieving both high light transmittance and low resistivity.
[0020] Preferably, the transparent top electrode layer is formed by stacking a buffer layer and an ultra-thin metal layer, and its thickness is 6-30nm; the buffer layer is an oxide or sulfide buffer layer; the buffer layer material includes one or more of MoO3, ZnO, WO3, and ZnS.
[0021] More preferably, the transparent top electrode layer is formed by stacking a MoO3 layer and an Au layer, the MoO3 layer is close to the hole transport layer, and the Au layer is arranged on a side of the MoO3 layer away from the hole transport layer.
[0022] Furthermore, the thickness of the MoO3 layer is 2-12 nm; the thickness of the Au layer is 4-10 nm; more preferably, the thickness of the MoO3 layer is 4-6 nm; the thickness of the Au layer is 6-9 nm.
[0023] More preferably, the thickness of the MoO3 layer is 5 nm; the thickness of the Au layer is 8 nm.
[0024] Furthermore, the structural formula of the perovskite absorption layer is ABX3 type perovskite material, wherein A includes one or two of CH3NH3, HC(NH2)2, Rb or Cs, B is one or two of Sn or Pb, and X is one or more of Cl, Br or I.
[0025] Furthermore, the thickness of the semi-transparent perovskite solar cell layer is <3 cm, and the average transparency in the visible light range (360-780 nm) is ≥30%; The thickness of the thermochromic layer is 2-4 cm, the average visible light transparency at 20-30°C (25°C) is >70%, and the average visible light transparency at 40-65°C is <20%; The thickness of the colored transparent film layer is 0.01-2 mm.
[0026] In the above scheme, by limiting the thickness of each layer of the thermochromic perovskite smart photovoltaic window to a reasonable range of values, each layer can play a better synergistic role, thereby improving the overall performance of the thermochromic perovskite smart photovoltaic window.
[0027] Furthermore, the thermochromic layer changes between a colorless transparent state and a white opaque state as the temperature changes, the critical transition temperature is 25°C-45°C, and the color change time is less than 10 minutes; Preferably, the thermochromic layer comprises one or more of a thermochromic hydrogel or a thermochromic liquid crystal material; more preferably, the thermochromic hydrogel used in the thermochromic layer comprises one or both of hydroxypropyl cellulose and poly (N-isopropyl acrylamide); The material of the colored transparent film layer is selected from one or more of polyethylene terephthalate, polyvinyl chloride, polyethylene, polystyrene, polyester, polyimide, polymethyl methacrylate, ethylene-vinyl acetate copolymer and polycarbonate.
[0028] In the above scheme, by using the appropriate types of thermochromic layers and colored transparent film layers, each layer can play a better synergistic role, thereby improving the overall performance of the thermochromic perovskite smart photovoltaic window.
[0029] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned thermochromic perovskite smart photovoltaic window, wherein the semi-transparent perovskite solar cell layer, the thermochromic layer and the colored transparent film layer are connected by bonding or snap connection. Preferably, the snap connection is an elastic snap connection.
[0030] A thermochromic perovskite smart photovoltaic window provided by the present invention balances the transparency and photoelectric conversion efficiency of a semi-transparent perovskite solar cell by simulating the multi-layer skin structure of a chameleon. Ultimately, the thermochromic perovskite smart photovoltaic window can simultaneously have multiple functions of photovoltaic power generation, color change, and transparency change, and has high cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 X-ray diffraction spectra of different CsPbBr3 perovskite films obtained after the CsBr solution stays on the PbBr2 film (loading 10s, loading 15s, loading 20s) in the preparation process of the CsPbBr3 perovskite absorption layer of the present invention.
[0033] Figure 2 The scanning electron micrograph (SEM) and picture of the CsPbBr3 perovskite film obtained when the CsBr solution is allowed to stay on the PbBr2 film for an optimal time of 15 seconds during the preparation process of the CsPbBr3 perovskite absorber layer of the present invention.
[0034] Figure 3 Schematic diagram of the color-changing principle and process of thermochromic perovskite smart photovoltaic window.
[0035] Figure 4 The reversible color change process of the thermochromic HPC hydrogel layer and its transparency curve at 25℃ and 45℃.
[0036] Figure 5 It is the transparency curve of blue transparent PET film.
[0037] Figure 6 This is a diagram of the cyclic color change process of the thermochromic perovskite smart photovoltaic window of the present invention.
[0038] Figure 7 The transparency curves of the thermochromic perovskite smart photovoltaic window of the present invention at 25°C and 45°C.
[0039] Figure 8 Transparency curves of different ultra-thin metal electrode layers.
[0040] Fig. 9 Resistance distribution diagram of different ultra-thin metal electrode films.
[0041] Fig.10 JV curves of different CsPbBr3 semi-transparent perovskite solar cells.
[0042] Fig.11 Schematic diagram of the structure of the CsPbBr3 semi-transparent perovskite solar cell layer of Example 2.
[0043] Fig.12 This is a physical picture of the CsPbBr3 semi-transparent perovskite solar cell layer of the thermochromic perovskite smart photovoltaic window of Example 2 of the present invention, obtained from the top (Top-view) and bottom (Bottom-view) sides.
[0044] Fig.13 This is a transparency curve diagram of the CsPbBr3 semi-transparent perovskite solar cell layer of the thermochromic perovskite smart photovoltaic window of Example 2 of the present invention tested from both the top (Top-view) and the bottom (Bottom-view).
[0045] Fig.14 This is a graph showing the average visible light transparency change of the thermochromic perovskite smart photovoltaic window of Example 2 of the present invention at 25°C and 45°C during 100 cycles of color change.
[0046] Fig.15 These are the changes in (a) photoelectric conversion efficiency (PCE), (b) open circuit voltage (Voc), and (c) fill factor (FF) of the thermochromic perovskite smart photovoltaic window of Example 2 of the present invention during 100 cycles of color change. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The beneficial effects of the present invention will be described below in conjunction with specific embodiments.
[0049] In order to obtain a CsPbBr3 perovskite absorption layer with excellent performance, the present invention explores the preparation conditions of the CsPbBr3 perovskite absorption layer, using ITO as a transparent bottom electrode layer, forming an electron transport layer on the transparent bottom electrode layer, and spinning 1M PbBr2 / DMF solution on the electron transport layer at a speed of 4000 rpm for 30s, and then heating and annealing on a heating plate at 100°C for 30min. Then, 200μL of a CsBr solution with a concentration of 250mg / mL is dripped onto the above-mentioned PbBr2 film, and spin-coated for 30s after staying for a period of time. After heating and annealing on a heating plate at 250℃~300℃ for 5min, it is immersed in an isopropyl alcohol (IPA) solution for 30min, and then heated and annealed on a heating plate at 250℃~300℃ for 10~20min again to form a CsPbBr3 perovskite absorption layer. By adjusting the residence time of CsBr solution on PbBr2 film (10s, 15s, 20s), perovskite films of different qualities were obtained, and their X-ray diffraction spectra are shown in Figure 1 The CsPbBr3 perovskite film with a retention time of 15 seconds has high crystallinity, no impurities, and a large uniform grain size. The scanning electron microscopy (SEM) image of its upper surface is shown in Figure 2 shown.
[0050] Example 1
[0051] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) CsPbBr3 semi-transparent perovskite solar cell layer: ITO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. A 1M PbBr2 / DMF solution is spin-coated on the electron transport layer at a speed of 4000 rpm for 30 seconds, and then heated and annealed on a hot plate at 100°C for 30 minutes. Then 200μL of a CsBr solution with a concentration of 250mg / mL is dropped on the above PbBr2 film, left for 15 seconds, and then spin-coated for 30 seconds. After heating and annealing on a hot plate at 250°C~300°C for 5 minutes, it is immersed in an isopropyl alcohol (IPA) solution for 30 minutes, and then heated and annealed on a hot plate at 250°C~300°C for 10~20 minutes to form a CsPbBr3 perovskite absorption layer. A hole transport layer will then be deposited on the CsPbBr3 perovskite absorption layer. Finally, 5 nm MoO3 and 6 nm Au were sequentially evaporated on the hole transport layer to form an ultra-thin metallic transparent top electrode layer.
[0052] (2) Thermochromic hydrogel layer: HPC (2.0 g) and 0.1 M KCl were dissolved in 0.1 L of deionized water and stirred for 4 h to prepare an HPC hydrogel solution. The edges of the double-layer glass were fixed together using transparent glue and narrow glass strips. The HPC hydrogel solution was then injected and encapsulated to obtain a thermochromic hydrogel layer with a thickness of 2.2 cm.
[0053] (3) Assembly of thermochromic perovskite smart photovoltaic window: The yellow CsPbBr3 semi-transparent perovskite solar cell layer, thermochromic HPC hydrogel layer and blue transparent PET film layer (thickness 0.08 mm, average visible light transparency 56.6%) obtained in the above steps are stacked in sequence, and the yellow CsPbBr3 semi-transparent perovskite solar cell layer and the blue transparent PET film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0054] Example 2
[0055] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) CsPbBr3 semi-transparent perovskite solar cell layer: ITO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. A 1M PbBr2 / DMF solution is spin-coated on the electron transport layer at a speed of 4000 rpm for 30 seconds, and then heated and annealed on a hot plate at 100°C for 30 minutes. Then 200μL of a CsBr solution with a concentration of 250mg / mL is dropped on the above PbBr2 film, left for 15 seconds, and then spin-coated for 30 seconds. After heating and annealing on a hot plate at 250°C~300°C for 5 minutes, it is immersed in an isopropyl alcohol (IPA) solution for 30 minutes, and then heated and annealed on a hot plate at 250°C~300°C for 10~20 minutes to form a CsPbBr3 perovskite absorption layer. A hole transport layer will then be deposited on the CsPbBr3 perovskite absorption layer. Finally, 5 nm MoO3 and 8 nm Au were sequentially evaporated on the hole transport layer to form an ultra-thin metallic transparent top electrode layer.
[0056] (2) Thermochromic hydrogel layer: HPC (2.0 g) and 0.1 M KCl were dissolved in 0.1 L of deionized water and stirred for 4 h to prepare an HPC hydrogel solution. The edges of the double-layer glass were fixed together using transparent glue and narrow glass strips. The HPC hydrogel solution was then injected and encapsulated to obtain a thermochromic hydrogel layer with a thickness of 2.2 cm.
[0057] (3) Assembly of thermochromic perovskite smart photovoltaic window: The yellow CsPbBr3 semi-transparent perovskite solar cell layer, thermochromic HPC hydrogel layer and blue transparent PET film layer (thickness 0.08 mm, average visible light transparency 56.6%) obtained in the above steps are stacked in sequence, and the yellow CsPbBr3 semi-transparent perovskite solar cell layer and the blue transparent PET film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0058] Example 3
[0059] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) CsPbBr3 semi-transparent perovskite solar cell layer: ITO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. A 1M PbBr2 / DMF solution is spin-coated on the electron transport layer at a speed of 4000 rpm for 30 seconds, and then heated and annealed on a hot plate at 100°C for 30 minutes. Then 200μL of a CsBr solution with a concentration of 250mg / mL is dropped on the above PbBr2 film, left for 15 seconds, and then spin-coated for 30 seconds. After heating and annealing on a hot plate at 250°C~300°C for 5 minutes, it is immersed in an isopropyl alcohol (IPA) solution for 30 minutes, and then heated and annealed on a hot plate at 250°C~300°C for 10~20 minutes to form a CsPbBr3 perovskite absorption layer. A hole transport layer will then be deposited on the CsPbBr3 perovskite absorption layer. Finally, 5 nm MoO3 and 9 nm Au were sequentially evaporated on the hole transport layer to form an ultra-thin metallic transparent top electrode layer.
[0060] (2) Thermochromic hydrogel layer: Dissolve 1.0g of N-isopropylacrylamide, 2.5wt% of hydroxypropylcellulose and 0.02g of N,N-methylenebis(acrylamide) in 10ml of water, then add 0.02g of ammonium persulfate, stir evenly, and then add 20μl of N,N,N',N'-tetramethylethylenediamine to obtain a PNIPAM-HPC composite hydrogel solution. Use transparent glue and narrow glass strips to fix the edges of the double-layer glass together. Then inject the obtained hydrogel solution and encapsulate to obtain a PNIPAM-HPC thermochromic hydrogel layer with a thickness of 2.4cm.
[0061] (3) Assembly of thermochromic perovskite smart photovoltaic window: The yellow CsPbBr3 semi-transparent perovskite solar cell layer, thermochromic hydrogel layer and blue transparent PET film layer (thickness 0.08 mm, average visible light transparency 56.6%) obtained in the above steps are stacked in sequence, and the yellow CsPbBr3 semi-transparent perovskite solar cell layer and the blue transparent PET film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0062] Example 4
[0063] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) CsPbBr3 semi-transparent perovskite solar cell layer: ITO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. A 1M PbBr2 / DMF solution is spin-coated on the electron transport layer at a speed of 4000 rpm for 30 seconds, and then heated and annealed on a hot plate at 100°C for 30 minutes. Then 200μL of a CsBr solution with a concentration of 250mg / mL is dropped on the above PbBr2 film, left for 15 seconds, and then spin-coated for 30 seconds. After heating and annealing on a hot plate at 250°C~300°C for 5 minutes, it is immersed in an isopropyl alcohol (IPA) solution for 30 minutes, and then heated and annealed on a hot plate at 250°C~300°C for 10~20 minutes to form a CsPbBr3 perovskite absorption layer. A hole transport layer will then be deposited on the CsPbBr3 perovskite absorption layer. Finally, 1 nm Cu and 7 nm Au were sequentially evaporated on the hole transport layer to form an ultra-thin metallic transparent top electrode layer.
[0064] (2) Thermochromic hydrogel layer: HPC (2.0 g) and 0.1 M KCl were dissolved in 0.1 L of deionized water and stirred for 4 h to prepare an HPC hydrogel solution. The edges of the double-layer glass were fixed together using transparent glue and narrow glass strips. The HPC hydrogel solution was then injected and encapsulated to obtain a thermochromic hydrogel layer with a thickness of 2.2 cm.
[0065] (3) Assembly of thermochromic perovskite smart photovoltaic window: The yellow CsPbBr3 semi-transparent perovskite solar cell layer, thermochromic HPC hydrogel layer and red transparent polyvinyl chloride film layer (thickness 0.3 mm) obtained in the above steps are stacked in sequence. The yellow CsPbBr3 semi-transparent perovskite solar cell layer and the red transparent polyvinyl chloride film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0066] Example 5
[0067] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) FAPbBr3 semi-transparent perovskite solar cell layer: FTO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. 7.34 mg of MACl, 69.98 mg of FABr and 205.52 mg of PbBr2 are dissolved in 300 μL of DMSO / DMF mixed solution (volume ratio is 1:1). The FAPbBr3 precursor solution is spin-coated on the electron transport layer at a speed of 4000 rpm for 30 seconds, and then heated and annealed on a hot plate at 100°C for 30 minutes to form a FAPbBr3 perovskite absorption layer. Then, a hole transport layer is deposited on the FAPbBr3 perovskite absorption layer. Finally, an ultra-thin metal or ITO is deposited on the above hole transport layer as a transparent top electrode layer.
[0068] (2) Thermochromic hydrogel layer: HPC (2.0 g) and 0.1 M KCl were dissolved in 0.1 L of deionized water and stirred for 4 h to prepare an HPC hydrogel solution. The edges of the double-layer glass were fixed together using transparent glue and narrow glass strips. The HPC hydrogel solution was then injected and encapsulated to obtain a thermochromic hydrogel layer with a thickness of 2.2 cm.
[0069] (3) Assembly of thermochromic perovskite smart photovoltaic window: The yellow FAPbBr3 semi-transparent perovskite solar cell layer, thermochromic HPC hydrogel layer and blue transparent PET film layer (thickness 0.08 mm, average visible light transparency 56.6%) obtained in the above steps are stacked in sequence, and the FAPbBr3 semi-transparent perovskite solar cell layer and the blue transparent PET film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0070] Example 6
[0071] This embodiment provides a thermochromic perovskite smart photovoltaic window, and its manufacturing method includes the following steps: (1) CsPbCl 2.5 Br 0.5 Colorless and transparent perovskite solar cell layer: ITO is used as the transparent bottom electrode layer, and an electron transport layer is formed on the transparent bottom electrode layer. Then CsCl, CsBr, and PbCl2 are co-evaporated on the electron transport layer at a ratio of 1:1:2 at a rate of 5 Å / s, and heated and annealed on a hot plate at 150°C for 10 minutes to obtain a transparent and colorless CsPbCl 2.5 Br 0.5 Perovskite film. Then a hole transport layer is deposited on the perovskite absorption layer. Finally, an ultra-thin metal or ITO is deposited on the above hole transport layer as a transparent top electrode layer.
[0072] (2) Thermochromic hydrogel layer: HPC (2.0 g) and 0.1 M KCl were dissolved in 0.1 L of deionized water and stirred for 4 h to prepare an HPC hydrogel solution. The edges of the double-layer glass were fixed together using transparent glue and narrow glass strips. The HPC hydrogel solution was then injected and encapsulated to obtain a thermochromic hydrogel layer with a thickness of 2.2 cm.
[0073] (3) Assembly of thermochromic perovskite smart photovoltaic window: CsPbCl 2.5 Br 0.5 The colorless transparent perovskite solar cell layer, the thermochromic HPC hydrogel layer and the green transparent PET film layer (thickness 0.08 mm) are stacked in sequence. 2.5 Br 0.5 The colorless transparent perovskite solar cell layer and the green transparent PET film layer are respectively pasted on the upper and lower sides of the thermochromic hydrogel layer.
[0074] Test example
[0075] The performance of the thermochromic perovskite smart photovoltaic windows and different structural layers of Examples 1-4 were tested as follows: (1) Color change performance test of thermochromic perovskite smart photovoltaic window: The color change principle of the thermochromic perovskite smart photovoltaic window of the present invention is as follows: Figure 3 As shown in the figure, by simulating the skin structure of a chameleon, the yellow CsPbBr3 semi-transparent perovskite solar cell layer, the thermochromic HPC hydrogel layer and the blue transparent PET film layer are integrated to simultaneously achieve reversible transformation between yellow and green colors and two transparencies. The color change process of the thermochromic HPC hydrogel layer and the transparency curves at different temperatures (25°C and 45°C) are shown in the figure. Figure 4 The transparency curve of the blue transparent PET film is shown in Figure 5 shown.
[0076] The thermochromic perovskite smart photovoltaic windows of Examples 1-3 can achieve the same thermochromic effect. The color change process is as follows: Figure 6 As shown, under the condition of 25°C, the thermochromic perovskite smart photovoltaic window appears in a green transparent state; after heating at 45°C for 2 minutes, the color of the thermochromic perovskite smart photovoltaic window changes to a yellow opaque state; after cooling at 25°C for 2 minutes, the thermochromic perovskite smart photovoltaic window returns to its original green transparent state. As the temperature changes, the thermochromic perovskite smart photovoltaic window can achieve cyclic reversible changes between two colors and transparency states. The transparency curves of the thermochromic perovskite smart photovoltaic window of Example 2 in two states are shown in Figure 2. Figure 7 shown.
[0077] (2) Transparency test of ultra-thin metal transparent top electrode layer: Figure 8 Transparency curves of different ultra-thin metal transparent electrodes directly deposited on glass plates by evaporation. Figure 8 It can be seen that the ultra-thin metal transparent electrodes of Examples 1-4 all have high transparency in the visible light range, and the average transparency exceeds 40%.
[0078] (3) Conductivity test of ultra-thin metal transparent top electrode layer: Different ultra-thin metal transparent electrodes are directly deposited on the surface of transparent conductive glass ITO by evaporation, and the obtained IV slope is used to illustrate the conductivity of 0.09cm 2 The film resistance of different ultra-thin metal transparent electrodes is Fig. 9 As shown. Fig. 9 It can be seen that the ultra-thin metal transparent electrodes of Examples 1-4 all have high transparency in the visible light range, and the average transparency exceeds 40%.
[0079] (4) Power generation efficiency test of thermochromic perovskite smart photovoltaic window: Use solar simulator to test the JV curves of different CsPbBr3 semi-transparent perovskite solar cells, such as Fig.10 As shown in Figure 2. Different cell efficiencies are the photoelectric conversion efficiencies of the corresponding thermochromic perovskite smart photovoltaic windows. Fig.10 It can be seen that the photoelectric conversion efficiency of the thermochromic perovskite smart photovoltaic windows of Examples 1-4 are 5.12%, 7.08%, 4.3% and 8.35%, respectively, and the thermochromic perovskite smart photovoltaic window of Example 2 has the highest photoelectric conversion efficiency.
[0080] The schematic diagram of the structure of the CsPbBr3 semi-transparent perovskite solar cell prepared by the present invention based on 5nmMoO3 and 8nmAu as transparent electrodes is shown in the figure Fig.11 As shown, the battery effect observed from the top and bottom ends is as follows Fig.12 As shown, the transparency curve of the CsPbBr3 semi-transparent perovskite solar cell layer tested from the top and bottom ends of the present invention is as follows Fig.13 As shown, after calculation, its average visible light transparency (AVT) in the visible light range (360-780nm) is 53%. After calculation, its light energy utilization efficiency (LUE=PCE×AVT) is 4.43, achieving a good balance between transparency and efficiency.
[0081] (4) The performance of the thermochromic perovskite smart photovoltaic window of Example 2 was tested for cycle performance, as follows: The thermochromic perovskite smart photovoltaic window was placed under 25℃ and 45℃ for heating-cooling treatment. After 100 cycles of discoloration, the average visible light transparency of the thermochromic perovskite smart photovoltaic window was as follows: Fig.14 As shown. Fig.14 It can be seen that the average visible light transparency of the thermochromic perovskite smart photovoltaic window at 25°C and 45°C remains almost unchanged, and it has excellent optical cycling stability.
[0082] After 100 cycles of discoloration, the photoelectric performance of the thermochromic perovskite smart photovoltaic window is as follows: Fig.15 As shown. Fig.15 It can be seen that compared with the initial state, the thermochromic perovskite smart photovoltaic window of the present invention still maintains 88% of the initial efficiency (PCE) after 100 cycles of discoloration, and the current density (Jsc) and fill factor (FF) remain at 93% of the initial state, and the open circuit voltage is almost unchanged compared with the initial state. The thermochromic perovskite smart photovoltaic window of the present invention has high photoelectric cycle stability.
[0083] Furthermore, the thermochromic perovskite smart photovoltaic windows of Examples 5-6 can achieve the same technical effects as those of Examples 1-4 above.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A thermochromic perovskite smart photovoltaic window, characterized in that: The invention comprises a semi-transparent perovskite solar cell layer, a thermochromic layer and a colored transparent film layer which are stacked in sequence; the semi-transparent perovskite solar cell layer and the colored transparent film layer have different colors.
2. The thermochromic perovskite smart photovoltaic window according to claim 1, characterized in that: The color of the semi-transparent perovskite solar cell layer includes yellow, red, blue or colorless and transparent; the color of the colored transparent film layer includes blue, red, yellow, green or purple.
3. The thermochromic perovskite smart photovoltaic window according to claim 1 or 2, characterized in that: The semi-transparent perovskite solar cell layer satisfies at least one of the following characteristics (1)-(3): (1) The average visible light transparency in the visible light range of 360-780nm is >30%; (2) Photoelectric conversion efficiency is >1%; (3) The sunlight utilization efficiency (LUE) value is 2.0-6.
0.
4. The thermochromic perovskite smart photovoltaic window according to any one of claims 1 to 3, characterized in that: The semi-transparent perovskite solar cell layer includes a transparent bottom electrode layer, an electron transport layer, a perovskite absorption layer, a hole transport layer and a transparent top electrode layer stacked in sequence, and the stacking method includes a formal structure and a transverse structure.
5. The thermochromic perovskite smart photovoltaic window according to claim 4, characterized in that: The transparent top electrode layer has an average visible light transparency of >50% in the visible light range of 360-780nm and a square resistance of <20Ω / m 2 ; Preferably, the material of the transparent top electrode layer includes one or more of metal, metal oxide, conductive polymer, and graphene; More preferably, the transparent top electrode layer is formed by stacking a buffer layer and an ultra-thin metal layer, and the buffer layer is an oxide buffer layer or a sulfide buffer layer; preferably, the buffer layer includes one or more of MoO3, ZnO, WO3, ZnS, and the ultra-thin metal layer includes one or more of Au, Ag, Al, Cu, Cr.
6. The thermochromic perovskite smart photovoltaic window according to claim 5, characterized in that: The transparent top electrode layer is formed by stacking a MoO3 layer and an Au layer, and its thickness is 6-30nm. The Au layer is arranged on the side of the MoO3 layer away from the hole transport layer; Preferably, the thickness of the MoO3 layer is 2-12 nm; the thickness of the Au layer is 4-15 nm.
7. The thermochromic perovskite smart photovoltaic window according to claim 4, characterized in that: The material of the transparent bottom electrode layer includes one or more of ITO, FTO and AZO, and the thickness thereof is 90-120 nm; The material of the electron transport layer includes one or more of SnO2, PCBM, ZnO, and TiO2, and its thickness is 20-60nm; The perovskite absorption layer has a structural formula of ABX3 type perovskite material, wherein A includes one or more of CH3NH3, HC(NH2)2, Rb or Cs, B is one or both of Sn or Pb, X is one or more of Cl, Br or I, and the thickness of the perovskite absorption layer is 80-500nm; The material of the hole transport layer includes one or more of Spiro-OMeTAD, PTAA, SAM-type single molecules, PEDOT:PSS, and nickel oxide, and the thickness thereof is 100-200 nm.
8. The thermochromic perovskite smart photovoltaic window according to claim 1, characterized in that: The thickness of the semi-transparent perovskite solar cell layer is <3 cm, and the average transparency in the visible light range of 360-780 nm is ≥30%; The thickness of the thermochromic layer is 2-4 cm, the average visible light transparency at 20-30° C. is >70%, and the average visible light transparency at 40-65° C. is <20%; The thickness of the colored transparent film layer is 0.01-2 mm.
9. The thermochromic perovskite smart photovoltaic window according to claim 1, characterized in that: The thermochromic layer changes between a colorless transparent state and a white opaque state as the temperature changes, the critical transition temperature is 25°C-45°C, and the color change time is less than 10 minutes; Preferably, the thermochromic layer comprises one or more of a thermochromic hydrogel or a thermochromic liquid crystal material; more preferably, the thermochromic hydrogel used in the thermochromic layer comprises one or both of hydroxypropyl cellulose and poly (N-isopropyl acrylamide); The material of the colored transparent film layer is selected from one or more of polyethylene terephthalate, polyvinyl chloride, polyethylene, polystyrene, polyester, polyimide, polymethyl methacrylate, ethylene-vinyl acetate copolymer and polycarbonate.
10. The method for preparing the thermochromic perovskite smart photovoltaic window according to any one of claims 1 to 9, characterized in that: The semi-transparent perovskite solar cell layer, the thermochromic layer and the colored transparent film layer are connected by bonding or snap connection.
Citation Information
Cited By
Luminescent solar concentrator with photovoltaic and dimming functions and preparation method thereof
CN121038558A
Self-adaptive color-changing semitransparent perovskite battery and preparation method and application thereof
CN121218769A
